FINANCIAL EQUALIZATION TRANSFERS BETWEEN PUBLIC AUTHORITIES BUDGETS - Emilia Cornelia STOICA (Challenges of the Knowledge Society)
This paper presents financial balancing mechanisms that it is applied by the most of the states with competitive market economy, in order to ensure equity between local authorities, as well as the stability of the entire national tax and budgetary system. In this regard, it is described the concept of financial equalization and its structure according to two fundamental criteria: - equalization in accordance with the financial transfers orientation, distinguishing thus (1) horizontal equalization, which is carried out between local authorities and consists in assigning a part of the richest territorial collectivities resources to the disadvantaged ones; (2) vertical financial equalization, achieved through consolidated transfers the state / federal budget to the budgets by territorial administrative units, both for the operating budget section and for the development one; - financial equalization according to the regional or local disparities observed as a result of territorial-level analyzes: (1) financial equalization based on balancing public revenues of the administrative-territorial units, which tries to correct the differences between the financial resources of each local authority and (2) the financial balancing based on the costs, which aims to reduce differences between standard costs of public services per capita. Financial equalization mechanisms have as main objective the reduction as far as the total elimination of the regional or local disparities, which are also described in this article.